Inggris - Abdillah, Muhammad Torieq; Naufal, Yamani; Syifa, Dian May (Institut Agama Islam Negeri Kendari, 2026)
The Free Nutritious Meal (MBG) program initiated by the Prabowo-Gibran government is a strategic effort to overcome nutrition problems and improve the quality of human resources in Indonesia. However, its implementation faces serious challenges in the form of cases of mass poisoning, poor nutritional quality, and uneven distribution. This study aims to analyze the MBG program through the lens of two legal philosophies: the Rechtsstaat (state of procedural law) of F.J. Stahl and al-maṣlaḥah al-‘āmmah (public interest) of Ibn Taymiyah. This study uses a normative legal method with a conceptual and comparative approach by testing the program's compliance with justice and public welfare. The findings of the study show that the implementation of MBG has not met the principles of the two thinkers. From Stahl’s perspective, cases of mass poisoning, weak checks and balances, and the absence of transparent legal accountability represent the state’s failure to protect fundamental rights and uphold the principles of law-based governance (wetmatigheid van bestuur). From Ibn Taymiyyah’s perspective, centralistic inefficiency and distribution injustice are evidence of a disregard for public trust and a violation of the principle of comprehensive justice (al-‘adl). The synthesis of the research concludes that the success of MBG requires the integration of Stahl’s procedural-legal framework with Ibn Taymiyah's moral-substantive values, which demand legal accountability as well as ethical-religious responsibility in accordance with Indonesia’s philosophy as a religious nation-state